Regulation of connective tissue growth factor (ccn2; ctgf) gene expression in human mesangial cells: modulation by HMG CoA reductase inhibitors (statins). Issue 3 (1st June 2001) - Goppelt-Struebe, M; Hahn, A; Iwanciw, D; Rehm, M; Banas, B
Abstract : Aim —Connective tissue growth factor (ccn; ctgf) gene expression is upregulated in fibrotic renal glomeruli. Therefore, the regulation and pharmacological modulation of ccn2 (ctgf) mRNA expression was investigated in a human renal mesangial cell line. Methods —A human renal mesangial cell line was cultured in vitro under standard conditions. After stimulation, RNA was extracted and ccn2 (ctgf) mRNA expression assessed by northern blot analysis. Results —The expression of ccn2 (ctgf) mRNA was transiently upregulated by fetal calf serum. Very rapid onset but short lasting ccn2 (ctgf) mRNA expression was observed after stimulation with lysophosphatidic acid, a bioactive lipid, which activates G protein coupled receptors. Induction of ccn2 (ctgf) mRNA expression by transforming growth factor β (TGF-β) was more prolonged and lasted for more than one day. The small GTPases of the Rho family were essential for basal as well as induced ccn2 (ctgf) expression: preincubation of the cells with toxin B from Clostridium difficile abrogated ccn2 (ctgf) mRNA expression. HMG CoA reductase inhibitors, which are therapeutically used as lipid lowering drugs, interfere with the isoprenylation and thus activation of Rho proteins. Simvastatin, an HMG CoA reductase inhibitor, inhibited ccn2 (ctgf) mRNA expression in a concentration dependent manner (IC50 : 1–2 μM). Conclusion —Statins were identified as potent inhibitors of ccn2 (ctgf) mRNA expression in mesangial cells, and therefore might be of potential use to modulate the excessive ccn2 (ctgf) expression in mesangial cells related to glomerular fibrosis.